Some Aspects of Mast Cells Carboxypeptidase A3 Participation in the Pathogenesis of COVID-19 - Andrey V. Budnevsky; Sergey N. Avdeev; Evgeniy S. Ovsyannikov; Nadezhda G. Alekseeva; Victoria V. Shishkina; Inessa A. Savushkina; Inna M. Perveeva; Sofia N. Feigelman; Avag G. Kitoyan; Valeria R. Drobysheva (International Journal of Biomedicine, 2023)
Background: This study aimed to determine the involvement of carboxypeptidase A3 (CPA3) in developing lung damage in patients with COVID-19. Methods and Results: The study included samples of autopsy material from the lungs of patients who died as a result of severe COVID-19 (the main group [MG] and persons who died from external causes (the control group [CG]). Immunohistochemical staining for CPA3 was carried out. A quantitative study of CPA3-positive mast cells (MCs) and the degree of their degranulation was carried out using a ×40 objective lens with an analysis of ≥50 fields of view with further conversion to 1 mm². Significant representation of CPA3-positive MCs per 1 mm2 of CPA3-positive MCs, CPA3-positive MCs with signs of degranulation (SD), and co-adjacent MCs was found in the MG compared to the CG (P=0.01 in all cases). In the main group, positive correlations were identified between the total number of CPA3-positive MCs, CPA3-positive MCs with SD and the blood hemoglobin level shortly before death (r=0.491 [P=0.008] and r=0.521 [P=0.004], respectively). Co-adjacent CPA3-positive MCs were negatively correlated with blood eosinophils at the beginning of hospitalization (r=-0.420 [P=0.023]). Also, the number of separately lying, CPA3-positive MCs negatively correlated with the blood monocyte shortly before death (r=-0.384 [P=0.044]). A positive correlation was established between the total number of CPA3-positive MCs, CPA3-positive MCs with SD, and adjacent CPA3-positive MCs with total blood protein in patients at the beginning of hospitalization (r=0.431 [P=0.020], r=0.449 [P=0.015] and r=0.456 [P=0.013], respectively). In addition, the study demonstrated a positive correlation between CPA3-positive MCs with SD and the total number of CPA3-positive MCs with blood aPTT levels (r=0.304 [P=0.045] and r=0.375 [P=0.045], respectively). A negative correlation was also found between the total number of CPA3-positive MCs and the blood INR level (r=-0.812 [P=0.050]). Finally, in patients at the beginning of hospitalization, a negative correlation was found between CPA3-positive MCs with SD, CPA3-positive MCs without SD, separately located CPA3-positive MCs, adjacent CPA3-positive MCs, and the total number of CPA3-positive MCs with blood amylase (r=-0.550 [P=0.002], r=-0.452 [P=0.045], r=-0.485 [P=0.030], r=-0.622 [P=0.008], and r=-0.590 [P=0.006], respectively). Conclusion: Our study identifies the potential involvement of CPA3 in the pathogenesis of severe COVID-19. However, many aspects of its participation remain unclear and require further study.